2021
DOI: 10.3389/fmed.2020.576820
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Method Study to Explore Ethical Dilemmas and Health Care Workers' Willingness to Work Amid COVID-19 Pandemic in Palestine

Abstract: Background: The high potential risks involved in working in a healthcare setting during a pandemic and the associated fear that may affect health care workers' (HCWs') willingness to work are important to understand to eliminate potential barriers to working. This study aimed to assess Palestinian HCWs' willingness to work and the related factors as well as to explore their ethical dilemmas during the coronavirus disease 2019 (COVID-19) pandemic.Materials and Methods: Quantitative (survey questionnaire) and qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
64
1
11

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(83 citation statements)
references
References 39 publications
7
64
1
11
Order By: Relevance
“…Moreover, due to the political situation in Palestine, many young men are employed in Israel. This plays an essential role in the initial spread surge within the population [33].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, due to the political situation in Palestine, many young men are employed in Israel. This plays an essential role in the initial spread surge within the population [33].…”
Section: Discussionmentioning
confidence: 99%
“…As the service providers, the employees working in the banks have more vulnerability toward prevailing hazards of COVID-19 due to the frequent human-to-human interactions. Similarly, we do find literature focusing on the stress and mental health of healthcare workers and its impact on their burnout ( Luceño-Moreno et al, 2020 ; Yıldırım and Solmaz, 2020 ), work life balance ( Magnavita et al, 2020 ), psychological wellbeing and anxiety ( Denning et al, 2021 ; Galbraith et al, 2021 ; Mo et al, 2021 ), and their willingness to work ( Maraqa et al, 2020 ) during the COVID-19 pandemic. However, very little is known about the impact of stress due to COVID-19 (COVID-19 STR) on the performance of banking staff who had to be available on duty during these tough times.…”
Section: Introductionmentioning
confidence: 95%
“…Finally, a survey of 550 frontline hospital workers in multiple disciplines in Palestine found that 25% of survey respondents were not willing to work during a pandemic, though physicians and nurses expressed this feeling less often than other healthcare workers. 33 Those with more longevity and lower stress levels were less likely to consider abandoning the workplace. Healthcare workers felt poorly prepared for COVID-19 care, unappreciated, and frustrated by unfair work distribution.…”
Section: Discussionmentioning
confidence: 99%